Heavy Metals Accumulation and Phytoremediation Ability of Onion (Allium cepa) and Garlic (Allium sativum) Grown on Contaminated Soils from Challawa Industrial Estate, Kano, Nigeria - I. Alkali; A. A. Audu; U. Bello; S. M. Darma; A. T. Ahmad (Journal of Applied Sciences and Environmental Management, 2022)
This work was designed to assess and compare the heavy metals accumulation and phytoremediation ability of some allium species (Garlic; Allium sativum and Onion; Allium cepa) grown on two different soils (contaminated and Control soils) using standard methods. Heavy metals (of Cr, Fe, Mn, Ni, Pb, and Zn) Concentrations (mg/Kg) were determined using atomic absorption spectrophotometry (AAS Model: 210VGP). Plants growth and biomass production were assessed. Biological concentration factors (BCF) and translocation factors (TF) were calculated. The mean levels of elements obtained ranged widely from 0.55 mg/Kg Ni to 1830.64 mg/Kg Fe. The results showed that onion accumulated higher concentrations of all the heavy metals compared to garlic with exception of Zn. However, the differences in heavy metal concentrations where significant only in Cr and Mn. Phytoremediation efficiency indices (BCF and TF) showed a similar trend for both onion and garlic. The mean BCF values of Pb, Cr, Zn, Mn and Fe in onion were generally high > 1. Ni and Pb had their mean TF values greater than 1. Thus, onion can be used as potential phytoextraction plant. The similarities in most of these metal accumulation trends, BCF and TF between onion and garlic might be due to their being similar species with similar physiological features and from the same family.